Enabling effective electrochemical healing of structural steel. Issue 2 (12th May 2021) - Hsain, Zakaria; Jiang, Zhimin; Pikul, James H
Abstract: Low-carbon steel is a widely used structural metal that, when fractured, can be repaired with high temperature processes. There are many applications, however, that would benefit from a room-temperature repair process which maintains the steel microstructure and prevents nearby materials and electronics from overheating. This work seeks to enable effective room-temperature healing of steel by understanding how ion transport and electrolyte chemistry influence growth morphology and strength in fractured steel struts repaired with nickel electrodeposition. Experiments and simulations show that pulsed electroplating mitigates diffusion-limited growth to enable smooth and dense nickel deposits that have 4× higher adhesion to steel than nickel deposited by potentiostatic electroplating. By combining pulsed electroplating and electrolyte chemistry selection, fully fractured steel wires could be repaired to achieve up to 69% of their pristine wire strength. Finally, a simple geometric model highlights the advantageous energy and time requirements of electrochemical healing across length scales.